N-acetyl-D-glucosamine-coated polyamidoamine dendrimer promotes tumor-specific B cell responses via natural killer cell activation - Hulikova, Katarina; Svoboda, Jan; Benson, Veronika; Grobarova, Valeria; Fiserova, Anna (International immunopharmacology, 2011)
N-acetyl-D-glucosamine-coated polyamidoamine dendrimer (GN8P), exerting high binding affinity to rodent recombinant NKR-P1A and NKR-P1C activating proteins, was shown previously to delay the development of rat colorectal carcinoma as well as mouse B16F10 melanoma, and to potentiate antigen-specific antibody formation in healthy C57BL/6 mice via NK cell stimulation. In this study, we investigated whether GN8P also modulates tumor-specific B cell responses. Serum anti-B16F10 melanoma IgG levels, IgG2a mRNA expression, antibody dependent cell-mediated cytotoxicity (ADCC), and counts of plasma as well as antigen presenting B cells were evaluated in tumor-bearing C57BL/6 mice treated with GN8P and in respective controls. To reveal the mechanism of GN8P effects, the synthesis of interferon-gamma (IFN-γ) and interleukin-4 (IL-4), cytokines involved in regulation of immunoglobulin class switch, was determined. The GN8P treatment significantly elevated IgG, and particularly IgG2a, response against B16F10 melanoma, which led to augmented ADCC reaction. The significant increase in production of IFN-γ, which is known to support IgG2a secretion, was observed solely in NK1.1 expressing cell populations, predominantly in NK cells. Moreover, GN8P raised the number of plasma cells, and promoted antigen presenting capacity of I-A/I-E-positive B lymphocytes by up-regulation of their CD80 and CD86 co-stimulatory molecule expression. These results indicate that GN8P-induced enhancement of tumor-specific antibody formation is triggered by NK cell activation, and contributes to complexity of anticancer immune response involving lectin-saccharide interaction.
Keywords: upregulace; Acetylglucosamine; B7-1 Antigen; Up-Regulation; imunoglobulin G; antigeny CD80; Dendrimers; Female; zvířata; myši; myši inbrední C57BL; B-lymfocyty; buňky NK; Mice; Killer Cells, Natural; acetylglukosamin; Interleukin-4; ženské pohlaví; antigeny CD86; B-Lymphocytes; Mice, Inbred C57BL; dendrimery; buněčná cytotoxicita závislá na protilátkách; Antibody-Dependent Cell Cytotoxicity; nádorové buněčné linie; interleukin-4; interferon gama; Animals; Cell Line, Tumor; Melanoma, Experimental; melanom experimentální; Immunoglobulin G; B7-2 Antigen; Interferon-gamma